Artists and Performance - Video and Film. (London : Tate Gallery Publications Department., 1981)
Nan Hoover ; Tina Keane ; Tamara Krikorian ; Marceline Mori ; Philippa Brown ; David Hall ; Richard Layzell ; David Critchley ; Kevin Atherton ; Mick Hartney ; Stuart Brisley ; Ken McMullen ; Ian Bourn ; Vito Acconci ; Robert Morris ; Bruce Nauman ; Lee Jaffe ; Stuart Brisley ; Barry Flanagan
vol. 2: Video and Film: Nan Hoover, Tina Keane, Tamara Krikorian, Marceline Mori, Philippa Brown, David Hall, Richard Layzell, David Critchley, Kevin Atherton, Mick Hartney, Stuart Brisley, Ken McMullen, Ian Bourn, Vito Acconci, Robert Morris, Bruce Nauman, Lee Jaffe, Stuart Brisley, Barry Flanagan
Engels
Artists and Performance, Video and Film, Tate Gallery, London, 22 September - 11 October 1981
boek
Keywords: Chaimowicz, Marc Camille; Hooker, Charlie